Pollution Load Analysis of Wonokromo River with Program System Dynamics (STELLA) - Filial Dhiya Thifalina; Badrus Zaman; Anik Sarminingsih (Universitas Diponegoro, 2023)
Population growth, the increase in the industrial sector and the presence of waste from activities that haven’t been treated properly can make a water river being contaimined high pollutants. The pollutant parameters identified is Total Suspended Solid (TSS), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO) and E.Coli. One of the polluted rivers is Wonokromo River which is located in Surabaya City, according from monitoring results Balai Besar Wilayah Sungai (BBWS) Brantas in 2021 the pollutant value in river with TSS is 484 mg/L, BOD is 15.96 mg/L, COD 23.91 mg/L, DO 3.67 mg/L, and E.coli 4.283 MPN/100 ml from the monitoring data included polluted category. Depectin model of water river conditions using the STELLA program. The results indicate that the water quality of the Wonokromo River is polluted with the parameters TSS, BOD and E. Coli, determination refers to Goverment Regulations number 22 in 2021 about “Implementation of Environmental Protection and Management” in clasification II for raw water. So Wonokromo River is not suitable as a source of raw water in that year and a policy scenario is needed to reduce water river pollution.